Analisis Kesiapan Penganggaran Household Atas Dampak Pandemi Covid-19 Di Indonesia - Muhammad Shareza Hafiz; Sri Fitri Wahyuni; Fiqi Ilham (Jurnal Riset AKuntansi dan Bisnis, 2021)
The purpose of this study is to identify and analyze the readiness of household budgeting and its factors for the impact of the Covid-19 pandemic in Indonesia. This research was conducted by a qualitative approach to phenomenological studies. The population of this study is a household in Indonesia which is selected using purposive sampling with judgment sampling method. The number of informants in this study were 8 informants with educational backgrounds from junior high school to master degree. The data analysis tool used was Manual Thematic Analysis using Interview Transcription. The results of this study are that there are differences in budgeting readiness during the Covid-19 pandemic and the majority of informants tend to be unprepared with household budgeting for the impact of Covid-19 in Indonesia and the factors consist of economic, education, and experience factor.